Software system for monitoring the situation in the settlement - Kundys, Serhii; Havano, Bohdan; Morozov, Mykola (Видавництво Львівської політехніки, 2022)
The goal of the work is to develop the software system of monitoring of a situation in the settlement. It consists of the user interface which is presented as a mobile application and the server. This paper describes the process of developing a client-server software system in stages using the latest technologies which will be relevant and easy to maintain in the future. The technologies used in the development process, the systems and modules which were integrated into the project, the main approaches to software development, as well as an explanation of why this particular stack of technologies was preferred for the implementation of this software system have been described. To make sure that developed mobile application meets common optimization requirements it has been tested for resources usage.
Keywords: client-server architecture; mobile development; software system; database; JavaScript; Node JS; React Native; Firebase